The Association of Genetic Variability in PNPLA3 with Histological Severity of Non-Alcoholic Fatty Liver Disease - Rotman, Yaron (2010)
BACKGROUND: Genome wide association (GWA) studies identified single nucleotide polymorphisms (SNPs) that are associated with increased hepatic fat or elevated liver enzymes, presumably reflecting nonalcoholic fatty liver disease (NAFLD). AIM: To investigate whether these SNPs are associated with histological severity in a large cohort of NAFLD patients. METHODS: 1117 (894 adults/223 children) individuals enrolled in NASH-Clinical Research Network and National Institutes of Health Clinical Center studies with histologically-confirmed NAFLD were genotyped for six SNPs that are associated with hepatic fat or liver enzymes in GWA studies. RESULTS: In adults, 3 SNPs on chromosome 22 showed associations with histological parameters of nonalcoholic steatohepatitis (NASH). After adjustment for age, gender, diabetes and alcohol consumption, the minor allele of rs738409C/G, a nonsynonymous coding SNP in the PNPLA3 (adiponutrin) gene encoding an I148M change, was associated with steatosis (p=0.03), portal inflammation (p=2.5×10(−4)), lobular inflammation (p=0.005), Mallory-Denk bodies (p=0.015), NAFLD activity score (NAS, p=0.004) and fibrosis (p=7.7×10(−6)). Two other SNPs in the SAMM50-PNPLA3 cluster demonstrated similar associations. Three SNPs on chromosome 10 in the CPN1-ERLIN1-CHUK region were independently associated with fibrosis (p=0.010). In children, no SNP was associated with histological severity. However, the rs738409 G allele was associated with younger age at the time of biopsy in multivariate analysis (p=0.045). CONCLUSIONS: In this large cohort of histologically-proven NAFLD, we confirm the association of the rs738409G allele with steatosis and describe its association with histological severity. In pediatric patients, the high-risk rs738409G allele is associated with an earlier presentation of disease. We also describe a hitherto unknown association between SNPs at a chromosome 10 locus and the severity of NASH fibrosis.